2005
DOI: 10.1519/16044.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Relative Intensities on Power Output During the Hang Power Clean: Identification of the Optimal Load

Abstract: The influence of different relative intensities on power output was investigated in the present study in order to identify the optimal load that maximizes power output during the hang power clean. Fifteen men (age: 22.1 +/- 2.0 years, height: 180.1 +/- 6.3 cm, and body mass: 89.4 +/- 14.7 kg) performed the hang power cleans on a forceplate at 30-90% of one repetition maximum (1RM). Peak power was maximized at 70% 1RM, which was, however, not significantly different from peak power at 50, 60, 80, and 90% 1RM. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
4
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(139 citation statements)
references
References 0 publications
11
121
4
2
Order By: Relevance
“…This finding is in contrast to previous research that indicated that PF increases in parallel with an increasing load. 7,8 However, it is possible that the decrease in PF at higher loads during the JS can be attributed to the breakdown of technique. It is possible that if the subjects had more training experience with the JS that their technique would remain unaffected at higher loads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in contrast to previous research that indicated that PF increases in parallel with an increasing load. 7,8 However, it is possible that the decrease in PF at higher loads during the JS can be attributed to the breakdown of technique. It is possible that if the subjects had more training experience with the JS that their technique would remain unaffected at higher loads.…”
Section: Discussionmentioning
confidence: 99%
“…Notes: PF, peak force; PV, peak velocity; PP, peak power; FPP, force at peak power; VPP, velocity at peak power; a , statistically different from value at 30% 1RM-HC (p < 0.05); b , statistically different from value at 30% 1RM-HC (p < 0.01); c , statistically different from value at 30% 1RM-HC (p < 0.001); d , statistically different from value at 45% 1RM-HC (p < 0.01); e , statistically different from value at 45% 1RM-HC (p < 0.001); f , statistically different from value at 65% 1RM-HC (p < 0.05) for PP production during PC and its variations. [4][5][6][7][8][9] However, this research has only examined either the PC from the floor [4][5][6]9 or the HC. 7,8 In line with previous research 1 , the current study demonstrated that the load that produced the greatest PP for the JS was 30% 1RM-HC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of powerlifters' intention to lift heavy loads as fast as possible, the ensuing velocity is slow due to the load and lift biomechanics (23). On the contrary, the Olympic lifts are performed at high velocities across the load spectrum (19). Findings from research studies have demonstrated that velocity specific adaptations in force and power occur even when voluntary effort is maximal (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic and kinetic data were calculated at the athletes' COM during unloaded trials and at the system COM (athlete + external load) during loaded trials. The kinematic and kinetic variables were calculated using the VGRF-time data and a forward dynamics approach reported previously in the literature (20,22,24). Briefly, trials were initiated with subjects standing erect and motionless.…”
Section: Methodsmentioning
confidence: 99%